Economic Base Analysis of Water-Energy-Food Sectors Using Location Quotient Techniques: A Case of West Java Province - Purwanto, Aries (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2017)
Water, energy and food are the most crucial sectors to be developed due to its importance for human life. The availability, accessibility, and quality of those three commodities have to be ensured for the whole people in a region. This research was conducted to study the existence of water, energy and food related sector compare with other sectors in West Java Province by using one of economic base approaches so called Location Quotient (LQ) method. By analysing gross regional domestic products (GRDP) year 2011-2015 at constant 2010 market prices, basic and non-basic sectors have been determined. The results show how the static and dynamic location quotient (SLQ & DLQ) analysis were effective to figure out general situation and characteristic of basic and non-basic sector in this region. This composite approach is expected to assist local government and stakeholders in undertaking preliminary evaluation in particularly water, energy and food sectors evaluation to improve their security. Furthermore, water, energy, and food related sectors mostly in quadrant III and IV, indicating that serious actions have to be taken particularly by local government to improve production of those basic commodities. Integrated measures are expected to maintain their availability in the forthcoming years.